Reimaging Human-Nature Interactions and Reclaiming Marginal Identity through Folk Narratives of Sundarbans1 - Biswas, Camellia (Nidān, 2022)
The folklore of the Sundarbans, including religious epics, is primarily disseminated through oral history, embodying the lived experience of marginalized communities. Popular Sundarban narratives of folk deities such as Bonbibi have already been discussed in various international fora, highlighting the Sundarbans as a domain of tragic human-tiger conflicts. However, the Sundarbans folklore also contain stories of other human-nature interactions, like the response to cyclones, floods, epidemics outbreaks, and attacks by crocodiles, sharks and venomous snakes. These more localized relationships are confined to smaller narratives that outline the everyday nature of human-nature conflicts, marked by coexistence and symbiosis. This paper focuses on the diverse epistemologies that are contained within the folk narratives of the Sundarbans, presented in the form of customary rituals, vrata-katha propitiatory texts, and thaan or small-shrine worship. Beginning by examining the functions of various folk deities in the Sundarbans, this paper describes their worship by Dalit and Adivasi communities. The deities have their own mythologies that describe typical hierarchized struggles, wherein marginalized deities attempt to enter the Brahmanical pantheon. Their struggle is similar to the struggle for dignity among their Dalit-Adivasi worshippers (referred to pejoratively through abusive epithets like chhotolok in colloquial Bengali), and accused of aspiring to become a so-called bhadralok.2 This paper highlights how marginalized populations structure the ‘narratives of marginal identity’ by commenting on mainstream Brahmanical religion. The argumentative thrust highlights how folk deity narrative traditions and practices are imbued with ecological knowledge that describe the community’s relationship with the environment. Folk stories constitute an important method of talking about the environment, its changes, and how people adjust to these changes. The paper concludes by defining the confrontation between folk narratives that are specific to microregions and their Brahmanical bhadralok hegemonic counterpart to produce a collective cultural heritage that give more centre stage position to marginalized epistemologies, deities, communities, and persons.